Efektivitas Penerapam Metode Hanifida Dalam Menghafal Al-Qur'an - Taufik, Muhammad; Darma, Surya Hadi; Setiawan , Usep (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KH. EZ. Muttaqien Purwakarta, 2024)
The lack of motivation of students to memorize the Al-Quran is something that is often found in various institutions, especially in institutions that have tahfidz programs. The Hanifida method as a technique for memorizing the Qur'an is expected to be able to improve the ability of students to memorize the Qur'an at the Darul Hikam Dormitory of Al-Hikamussalafiyah Cipulus Islamic Boarding School. This research uses a descriptive qualitative approach and method using observation and interview techniques with types and sources of data accompanied by triangulation as data analysis to get the focus of the problem being studied. Hanifida is used as a technique in memorizing the Quran to improve students' ability to memorize the Quran. Memorizing the Quran using the Hanifida technique can strengthen memorization because it is unique by containing images, keywords, formulas and stories when compared to other methods such as the ATIK and Tarjim methods. so that it makes it easier for students to feel happy in the process of memorizing the Quran. Â